Citizen monitoring of ambient dose rate: the SAFECAST project - Kuča, Petr; Helebrant, Jan; Bossew, Peter (Radiation protection dosimetry, 2023)
Citizen Science (CS) is research performed by citizens who are not professional scientists in general. SAFECAST was founded in Japan after the Fukushima accident 2011, motivated by distrust in the perceived biassed information by authorities about radiation situation. Measurements of ambient dose rate (ADR) performed by citizens were intended to verify and complement official data using bGeigieNano designed for purpose, recording ADR, GPS coordinates and date/time allowing projection on digital maps. The project expanded internationally, by mid-2022 containing ⁓180 million measurements. CS generates large amount of data as valuable source for science; it has educational value and serves communication between citizens and professionals. Problems consist in quality assurance (QA): citizens who are no trained metrologists are usually little familiar with notions of representativeness, measurement protocols and uncertainty that are the central QA topics. We discuss variability of response of instruments of the same kind under same ambient conditions and isotropy of response under field conditions.
Keywords: občanská věda; komunikace; lékaři; Citizen Science; Japan; lidé; Uncertainty; nejistota; Communication; Physicians; Japonsko; Humans